Transforming gender citizenship : the irresistible rise of gender quotas in Europe / edited by Eléonore Lépinard, Université de Lausanne, Ruth Rubio-Marin, University of Seville. - Lépinard, Éléonore; Rubio-Marín, Ruth (Cambridge studies in law and society., 2018)
Gender quotas are a controversial policy measure. However, over the past twenty years they have been widely adopted around the world and especially in Europe. They are now used in politics, corporate boards, state and local public administration and even in civil society organizations. This book explores this unprecedented phenomenon, providing a unique comparative perspective on gender quotas' adoption across thirteen European countries. It also studies resistance to gender quotas by political parties and supreme courts. Providing up-to-date comprehensive data on gender quotas regulations, Transforming Gender Citizenship proposes a typology of countries, from those which have embraced gender quotas as a new way to promote gender equality in all spheres of social life, to those who have consistently refused gender quotas as a tool for gender equality. Reflecting on divergences and commonalities across Europe, the authors analyze how gender quotas may transform dominant conception of citizenship and gender equality.